Influence of maturation stage on agility performance gains after plyometric training: a systematic review and meta-analysis - Asadi, A.; Arazi, H.; Ramirez-Campillo, R.; Moran, J.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2017)
Although plyometric training (PT) improves change of direction (COD) ability, the influence of age on COD gains after PT is unclear. Therefore, the aim of this systematic review was to identify the age-related pattern of improvement in COD ability after PT in youths. A computerized search within 6 databases was performed, selecting studies based on specific inclusion criteria: experimental trials published in English-language journals, PT focused on the lower-body, COD ability measurements reported before and after training, and male participants aged 10 to 18 years. Sixteen articles with a total of 30 effect sizes (ESs) in the experimental groups and 13 ESs in the control groups were included. For the analyses, subjects were categorized into 3 age groups: 10-12.9 years of age (PRE), 13-15.9 years of age (MID), and 16-18 years of age (POST). Independent of age, PT improved COD ability in youths (ES = 0.86, time gains [TG = -0.61]). However, a tendency toward greater COD ability gains was observed in older subjects (MID, ES = 0.95; POST, ES = 0.99) compared with younger subjects (PRE, ES = 0.68). Pearson product-moment correlation (r) indicated that 2-weekly sessions of PT-induced meaningful COD ability gains (for ES, r = 0.436; for TG, r = -0.624). A positive relationship was found between training intensity and ES (r = 0.493). In conclusion, PT improves COD ability in youths, with meaningfully greater effects in older youths. Two PT sessions per week, with 1,400 moderate-intensity jumps for 7 weeks, seems to be an adequate dose.